1988
DOI: 10.1084/jem.168.6.2361
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of heavy chain variable region subgroup use by human monoclonal autoantibodies of different specificity.

Abstract: In some of the earliest experiments proving the existence of crossreactive idiotypes (CRIs), Kunkel et al. (1) CRIs associated with the L and H chains ofCAs have also been described (reviewed in reference 4) . Many CAs bind to the I antigen, a developmentally regulated carbohydrate moiety on the erythrocyte membrane (5) . The CAs with anti-I specificity generally use VkIII L chains, which may also derive from the Humkv325 gene and/or closely related genes (2, 6). As both RFs and CAs frequently use the same Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 14 publications
0
26
1
Order By: Relevance
“…CLL B cells have been shown to express IgM Abs that display reactivity to self-proteins. In addition, several 51p1-encoded Ig expressed in CLL are polyreactive, having reactivity to IgG, cardiolipin, DNA, actin, and thyroglobulin (35)(36)(37)(38)(39)(40). Such polyreactivity is characteristic of some "natural" autoantibodies produced early in B cell development.…”
Section: Discussionmentioning
confidence: 99%
“…CLL B cells have been shown to express IgM Abs that display reactivity to self-proteins. In addition, several 51p1-encoded Ig expressed in CLL are polyreactive, having reactivity to IgG, cardiolipin, DNA, actin, and thyroglobulin (35)(36)(37)(38)(39)(40). Such polyreactivity is characteristic of some "natural" autoantibodies produced early in B cell development.…”
Section: Discussionmentioning
confidence: 99%
“…1). We have recently demonstrated that the great majority of d I I b RF (77%) use VHl-deriVed heavy chains (3). These H chains bear a CRI identified by MAb G6 (43).…”
Section: )mentioning
confidence: 99%
“…CLL B cells have been shown to express IgM Abs that display reactivity to self-proteins (27,61,62). In addition to SMI, several other 51p1-encoded Ig expressed in CLL are polyreactive, having reactivity to IgG, cardiolipin, DNA, actin, and thyroglobulin (23,(63)(64)(65)(66)(67). Several studies have postulated that CLL may arise from a clonal outgrowth of B cells (68,69), based on identification of the restricted use of certain D segments and J H genes in 51p1-encoded Ig expressed by CLL B cells encode a third complementarity determining region with conserved amino acid motifs (69).…”
Section: Discussionmentioning
confidence: 99%